Common Findings in Endoscopic Gastric Biopsies in Southeastern Anatolia: Effects of Eating Habits and Helicobacter Pylori Infection - Burçin Pehlivanoğlu; Bilge Aydın Türk; Serap İşler; Zülfükar Bilge (İstanbul Medical Journal, 2021)

(untitled)
Introduction:Roasted and spicy food (mainly hot pepper) consumption is very common in Southeastern Anatolia. Smoked and spicy diets and Helicobacter pylori (H. pylori) infection are known risk factors for gastric cancer. The aim of this study was to investigate the effects of eating habits on the gastric mucosa, to investigate the rate of H. pylori positivity, and to examine the association of these factors with histopathological features in this region.Methods:Histopathological findings in endoscopic biopsies of 943 consecutive patients were retrospectively evaluated.Results:More than half of the patients were female (54%; n=505), and the median age was 47±17.27 (range: 18-96). The most common non-gastritis histopathologic diagnosis was gastric carcinoma (2.5%; n=24), followed by polypoid lesions (1.6%; n=16). The vast majority of patients (92%) had chronic gastritis, and neutrophilic activity was present in 61% (n=537). The frequencies of atrophy, intestinal metaplasia, and regenerative mucosal changes were significantly correlated with the severity of neutrophilic activity (p<0.05). Patients with atrophy and intestinal metaplasia were significantly older than those without atrophy and intestinal metaplasia (p<0.001; mean age: 47 and 46 vs 56 and 55, respectively). More than 50% were infected with H. pylori (57%; n=542), and H. pylori positivity was associated with the presence of chronic and chronic active gastritis, as well as lymphoid hyperplasia (p<0.001). In contrast, erosion, atrophy, and neuroendocrine cell hyperplasia were less common in patients with H. pylori gastritis (p<0.05).Conclusion:H. pylori infection and spicy food consumption are key risk factors for gastritis in Southeastern Anatolia. Prospective epidemiological studies are needed to better demonstrate the causal interaction between dietary factors and gastritis.